Strategic Role of E-Public Procurements in the Formation of Sustainable and Inclusive Economy - Каламан, Ольга Борисівна; Kalaman, Olga В.; Каламан, О. Б.; Tkachenko, Nataliia; Kovalenko, Yuliia; Rodchenko, Larysa; Rodchenko, Igor (My University, 2023)
The purpose of this study is to develop proposals for the introduction of ecological, digital, professional, innovation and social public procurements in the national strategy on E-Public Procurement Reform and the strategy of procurements on the company-customer level. The relevance of this study is due to the need to ensure the development of “smart”, sustainable, inclusive economy, which will help reduce unemployment, poverty, facilitate access for people with disabilities to work, create opportunities for the education of young people and adults, stimulate innovations, meet expectations of citizens, solve environmental problems, carry out digital transformations taking into consideration the best world practices. The share of public procurements in expenditures of the state budget and gross domestic product of Ukraine, the dynamics of the procurement’s participants in the B2G segment is evaluated. In Ukraine, the largest share of expenditures falls on security and social protection, however, the prosperity index in these categories is critical (“red” zone). In order to form The E-Public Procurement Strategy, the best world practices of introducing innovative, environmental and social procurement criteria should be considered. Strategic directions of public procurement, namely – ecological, digital, professional, innovation and social, which provide sustainable and inclusive development of economy, are proposed.
Strategic Role of E-Public Procurements in the Formation of Sustainable and Inclusive Economy / N.Tkachenko, Y. Kovalenko, O. Kalaman, L. Rodchenko, I. Rodchenko, S. Didukh // Journal of Information Technology Management.- 2023, Vol. 15, №1. - P. 113-123. https://doi.org/10.22059/jitm.2023.90728
Keywords: E-Public Procurement; Public Procurement Strategy; Digital Procurement; Government Expenditures; Sustainable; Inclusive Economy; електронні державні закупівлі; стратегія державних закупівель; цифрові закупівлі; державні витрати; стійкість; інклюзивна економіка; Research Subject Categories::TECHNOLOGY; Research Subject Categories::SOCIAL SCIENCES::Business and economics